2022
DOI: 10.1101/2022.03.23.22272807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proof-of-concept: SCENTinel 1.1 rapidly discriminates COVID-19 related olfactory disorders

Abstract: The COVID-19 pandemic has increased the prevalence of people suffering from olfactory disorders. In the absence of quick, population-wide olfactory tests, we developed SCENTinel, a rapid, inexpensive smell test to assess odor detection, intensity, and identification ability, which can discriminate anosmia (e.g., total smell loss) from normosmia (e.g., normal sense of smell) using a single odor. A new version, SCENTinel 1.1, extends the original test with one of four possible odors and a hedonic subtest (how pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Even though this suggests that those subjects had some better smell and/or taste capabilities before COVID-19, lack of data on their pre-COVID-19 chemesthetic capabilities makes it impossible to precisely define to what degree their deficits were COVID-related, and what smell/taste qualities, and quantities were affected by COVID-19. This result also argues for the need for regular smell and taste screenings raised in other reports (Mainland et al, 2020;Hunter et al, 2023). Development and widespread use of relevant tests can benefit society, especially that it might help in early diagnosis of diseases in which smell loss is one of the symptoms, such as neurodegenerative diseases and accelerated cognitive decline (Albers et al, 2006;Dintica et al, 2019;Doty and Hawkes, 2019), or head trauma (Callahan and Hinkebein, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Even though this suggests that those subjects had some better smell and/or taste capabilities before COVID-19, lack of data on their pre-COVID-19 chemesthetic capabilities makes it impossible to precisely define to what degree their deficits were COVID-related, and what smell/taste qualities, and quantities were affected by COVID-19. This result also argues for the need for regular smell and taste screenings raised in other reports (Mainland et al, 2020;Hunter et al, 2023). Development and widespread use of relevant tests can benefit society, especially that it might help in early diagnosis of diseases in which smell loss is one of the symptoms, such as neurodegenerative diseases and accelerated cognitive decline (Albers et al, 2006;Dintica et al, 2019;Doty and Hawkes, 2019), or head trauma (Callahan and Hinkebein, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This was not explicitly discouraged or encouraged in the instructions. The SCENTinel ® odor detection and odor identification task (both its first and second attempt) were scored as dichotomies (i.e., correct/incorrect); the odor intensity rating was collected as a continuous variable and then scored as a dichotomy (i.e., ≤20 = smell loss; ≥21 = acceptable smell function) (8,34). The odor intensity cutoff of 20 was used based on a previous study that found that those who rated a moderate to strong odor <20 on a 1-100 scale was indicative of COVID-19 related smell loss (8,34).…”
Section: Methodsmentioning
confidence: 99%
“…The SCENTinel ® test is a rapid, accurate, inexpensive, and selfadministered screening test that combines assessments of three components of olfactory function: odor detection, odor intensity, and odor identification (29,34). The SCENTinel ® test card contains three boxes (A, B, or C) using Lift'nSmell technology (Scentisphere, Carmel, NY, United States).…”
Section: Scentinel®mentioning
confidence: 99%
See 2 more Smart Citations